PERANCANGAN SISTEM PENGAPIAN PADA ENGINE TRAINER CARRY ST 100 - , NANDA DEZI PUTRA; , Ir. Susanto Johanes., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Goals and making from this thesis is to make engine trainer as study tools, it designed by some consideration and good planning so that can to be easier to used by practitioner. As we studied before that Internal combustion engine result in energy by burning the air and fuel mixture in the cylinder. In gasoline engine, the spark jumps the spark plug is needed to ignite the air-fuel mixture that has been compressed by the piston in the cylinder. while the diesel engine air is compressed by the high pressure so that it becomes very hot, and when fuel is sprayed into the cylinder, will be burned simultaneously. Ignition system in the automobile serves to raise the battery voltage to 10 kV or more by using the ignition coil and then distribute the high voltage to each spark plug via the distributor and high voltage cables. This battery type ignition system used on all gasoline motors for modern cars. which is after finishing test and measuring the result show that all of the This thesis is an engine trainer that still use the conventional ignition system which The conventional ignition system still works mechanically by using platinum components and parts still good working.